PAYMENT INFORMATION SYSTEM FOR INCREASING EMPLOYEE WORKING EFFECTIVENESS IN PR TUNAS MANDIRI IN PACITAN REGENCY - Muhammad Ifan Fanani; Muhammad Oktoda Noorrohman; Arwin Datumaya Wahyudi Sumari (Informatika, Universitas Jenderal Soedirman, 2022)
Human capital management information system aims to improve the performance and to reduce errors in the existing business processes at human resources section to facilitate operational activities, especially in the case of employee data management, attendance, and salary calculations. The problem that is faced at this moment is in data management process, attendance, and leave where employee payroll system is the main problem. On the other hand, mobile-based information system will ease the business owner to control his employee’s performance, or the employees can do recaps. The developed information system is based on PIECES analysis that focuses on 6 aspects, namely Performance, Information and Data, Economy, Control and Security, Efficiency, and Service, and used Scrum software development method that includes storyboards based on the developed features, product backlog, and sprints. Based on the result analysis, the developed information system obtained average equation of interest and satisfaction in system usage from 50 respondents who are 86% from senior high school and 16% from bachelor’s degree, obtained the average level of satisfaction 100% for Performance, 95.72% for Information, 96.48% for Economics, 93.29% for Control, 94.56% for Efficiency, and 96.81% for Service. For User Satisfaction Questionnaire Tabulation, it is obtained an average of 4.21 for Performance domain, an average of 4.21 for Information domain, an average of 4.26 for Economics, an average of 4.17 for Control domain, an average of 4.23 for Efficiency domain, and an average of 4.08 for Service domain. The developed information system can improve the accuracy and the effectivity of employee data recording and attendance as well as speed up the employee salary calculation and reduce the error because it is already integrated with the employee attendance system.